2016
DOI: 10.1007/s12026-016-8798-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effects of mesenchymal stromal cells-derived exosome

Abstract: The mechanisms underlying immunomodulatory ability of mesenchymal stromal cells (MSCs) remain unknown. Recently, studies suggested that the immunomodulatory activity of MSCs is largely mediated by paracrine factors. Among which, exosome is considered to play a major role in the communication between MSCs and target tissue. The aim of our study is to investigate the effect of MSCs-derived exosome on peripheral blood mononuclear cells (PBMCs), especially T cells. We find that the MSCs-derived exosome extracted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
238
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 280 publications
(250 citation statements)
references
References 40 publications
10
238
1
1
Order By: Relevance
“…Thus, the lack of miR-223 within exosomes resulted in sepsis-induced heart failure, inflammation and death, while miR-223-containing exosomes attenuated the inflammatory response and minimized morality. These immune modulatory properties of MSC-derived exosomes are thus consistent with the findings by Chen et al (4).…”
supporting
confidence: 92%
See 4 more Smart Citations
“…Thus, the lack of miR-223 within exosomes resulted in sepsis-induced heart failure, inflammation and death, while miR-223-containing exosomes attenuated the inflammatory response and minimized morality. These immune modulatory properties of MSC-derived exosomes are thus consistent with the findings by Chen et al (4).…”
supporting
confidence: 92%
“…Previous studies had shown that MSC-derived exosomes promoted cellular proliferation (5) and indoleamine 2,3-dioxygenase (IDO) activity, but this study reported that proliferation and IDO activity was unaffected (8). Additionally in this study (4), apoptosis was found to be upregulated in both PBMCs and CD3+ T cells but not in prior studies (8). It should be noted that these discrepancies might be due to the different components that are carried within different types of exosomes or the underlying complexity that differentiates MSCs from MSC-derived exosomes and thus may significantly affect biological activities.…”
contrasting
confidence: 48%
See 3 more Smart Citations